Good News for Everyone - Frank, Penny; Nang Chan Yeema (Batavia, IL USA Lion Publishing, 1989)
After Jesus ascends into heaven, the apostles are visited by the Holy Ghost and go out to preach the word of Jesus and perform miracles.
Keywords: Juvenile Nonfiction